Mineralization, geochronology, and Pb isotope studies of the shoshonitic lava-hosted Nariniya Pb deposit, central Tibet: linking ore formation to post-collisional potassic magmatism. Issue 4 (11th March 2016) - Song, Yucai; Zhang, Chong; Tian, Shihong; Huang, Shiqiang; Zhuang, Liangliang
Abstract: A newly discovered, shoshonitic lava-hosted Pb deposit at Nariniya in central Tibet provides an excellent example to help improve our understanding of the linkage between post-collisional potassic magmatism and ore formation in Tibet. The Pb ores exist as veins or veinlets in NWW-striking fracture zones within the potassic lava (trachyte). The veins contain quartz, galena, pyrite, and sericite (muscovite) as well as minor chalcopyrite, sphalerite, calcite, and dolomite with sericitization, pyritization, and minor silicification. The 40 Ar– 39 Ar plateau age of the hydrothermal muscovite is 37.95 ± 0.30 Ma, which represents the Pb mineralization age. This obtained age is indistinguishable, within analytical error, from the zircon U–Pb age of 37.88 ± 0.22 Ma for potassic lava. Therefore, the ore formation can be genetically linked to potassic magmatism. Galena has similar Pb isotopic composition to magmatic feldspar from the host lava, suggesting the derivation of Pb from the magmatic system. Previous studies have suggested that S- and ore-forming fluids are of magmatic origin. Published data show that the Nariniya volcanic rocks are acidic, shoshonitic, akakitic, peraluminous, and enriched in Sr–Nd–Pb isotopes. Thus, they are geochemically different from other potassic volcanic rocks (no adakitic affinity) in the North Qiangtang terrane, but similar to the 46–38 Ma high-K calc-alkaline peraluminous adakitic rocks in this terrane and the late Eocene Cu-generating potassic porphyries from the Sanjiang region of eastern Tibet. As such, the Nariniya potassic magma likely originated from melting of subducted continental crust, with or without interaction with the overlying enriched mantle. Such post-collisional potassic rocks in Tibet are thought to be potential targets for prospecting of both Pb–Zn and porphyry Cu ores. Note that other ore styles (in addition to the Nariniya ore style) may exist in the potassic volcanic districts of Tibet.